2011
DOI: 10.1186/1471-2164-12-373
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and evolutionary changes in the antibiotic resistance of Burkholderia cenocepacia observed by global gene expression analysis

Abstract: BackgroundBurkholderia cenocepacia is a member of the Burkholderia cepacia complex group of bacteria that cause infections in individuals with cystic fibrosis. B. cenocepacia isolate J2315 has been genome sequenced and is representative of a virulent, epidemic CF strain (ET12). Its genome encodes multiple antimicrobial resistance pathways and it is not known which of these is important for intrinsic or spontaneous resistance. To map these pathways, transcriptomic analysis was performed on: (i) strain J2315 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 66 publications
3
64
0
Order By: Relevance
“…Here, we have thoroughly characterized the metabolism of the type strains of B. cenocepacia and B. multivorans. Our network reconstructions can be used to contextualize high-throughput transcriptomic and proteomic data (58,(74)(75)(76)(77) to provide further insight into gene regulation and downstream phenotypes. Additionally, our reconstructions can be used as established starting points to analyze pathogenesis and physiology of the growing list of sequenced Burkholderia strains, including both clinical and environmental isolates (78).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have thoroughly characterized the metabolism of the type strains of B. cenocepacia and B. multivorans. Our network reconstructions can be used to contextualize high-throughput transcriptomic and proteomic data (58,(74)(75)(76)(77) to provide further insight into gene regulation and downstream phenotypes. Additionally, our reconstructions can be used as established starting points to analyze pathogenesis and physiology of the growing list of sequenced Burkholderia strains, including both clinical and environmental isolates (78).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the expression of QS genes in isolates from patients A and B matched the microarray data. Virulence factors, such as motility, T3SS, and exopolysaccharides, are QS dependent, and their orchestrated regulation in Bcc bacteria was previously reported (19,20). In the context of our test condition (the biological origin of the isolate), we presumed that their significant gene expression changes had important implications for survival in the bloodstream and contributed to bacterial cell defense against the host immune system.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, the Chi-square independence test indicated that the 73 genes were significantly associated with environment conditions (p <0.001). Higher transcriptional activities of these induced genes under CF-like conditions could indicate that there are adaptive changes for these genes, which facilitates this species to transmit infections among CF patients (Drevinek et al 2008;Sass et al 2011). Taken together, the CF environment transition in B. cenocepacia could give rise to the codon usage bias in these highly expressed genes, and these highly expressed genes showed environmental adaptation to the CF environment.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, we searched the homology of these 826 genes against some functionally confirmed drug-resistance related genes at NCBI (www.ncbi.nlm.nih.gov), and we detected a substantial number of related genes (Supplementary Table S3), e.g., a gene for MFS_1 which belongs to the MFS that facilitates transport across cytoplasmic or internal membranes of a variety of substrates (Holden et al 2009); glnP, which encodes an ABC transporter permease protein that is associated with multidrug resistance (Moussatova et al 2008); emrB, which encodes a member of the drug resistance transporter EmrB/QacA subfamily (Ma et al 1994) and matE, which encodes a MATE efflux family protein that functions in MATE (Holden et al 2009). In responses to treatment with antimicrobial compounds, genes from drug resistance-related systems are under selection pressure in the long term (Cowen and Lindquist 2005;Sass et al 2011). Then a rapid evolution of virulence and drug resistance-related genes will emerge in the infectious pathogens (Cowen and Lindquist 2005).…”
Section: Discussionmentioning
confidence: 99%